Community health volunteer support for regular blood pressure monitoring in Indonesia: spatial regression models - Mayumi Mizutani; Sofi Oktaviani; Harumi Bando; Heri Sugiarto; Ritsuko Nishide; Susumu Tanimura (Tropical Medicine and Health)
Abstract Background Community-based blood pressure monitoring is essential for effective hypertension management, especially in low- and middle-income countries like Indonesia, where community health volunteers (CHVs) are vital. However, there is a lack of strong evidence regarding which aspects of CHV support are most effective at encouraging regular blood pressure monitoring. This study examined the spatially adjusted relationship between the prevalence of regular blood pressure monitoring and the specific traits of Indonesian CHV support. Methods The researchers conducted an ecological study utilizing sub-district level data from the fifth wave of the Indonesian Family Life Survey. The analysis included data on 25,829 individuals across 1774 sub-districts, with a focus on 612 CHVs in 259 sub-districts. To explore the spatially adjusted relationships between regular blood pressure monitoring and 16 CHV traits, ordinary regression and spatial regression models were employed. Additionally, geographically weighted regression (GWR) was implemented to examine geographical variations in the strength of these associations. Results The overall prevalence of regular blood pressure monitoring across the 1774 sub-districts was 17.5%. Regression models revealed positive associations between this prevalence and CHVs being described as “considerate and kind” (B = [3.85, 4.24], p = 0.038–0.048) and “helpful” (B = [4.60, 4.82], p = 0.038–0.041). The GWR analysis showed notable variations in regression coefficients, with “considerate and kind” yielding B = [3.79, 4.07] and “helpful” yielding B = [4.42, 4.79], both demonstrating stronger associations in the western and northern region of Sumatra Island. Meanwhile, “values artistic/aesthetic experiences” showed a negative association, significant only in spatial regression models (B = [− 2.47, − 2.44], p = 0.046–0.048). Conclusions This study emphasized the crucial role that CHVs play in promoting regular blood pressure monitoring in Indonesia. Compassion, kindness, and helpfulness were especially vital for improving community-based blood pressure monitoring, which leads to the better management of hypertension.